Correction of B1-inhomogeneities for relaxation-compensated CEST imaging at 7 T - Windschuh, Johannes; Zaiss, Moritz; Meißner, Jan-Eric; Paech, Daniel; Radbruch, Alexander; Ladd, Mark E.; Bachert, Peter (NMR in biomedicine, 2015)
Chemical exchange saturation transfer (CEST) imaging of endogenous agents in vivo is influenced by direct water proton saturation (spillover) and semi-solid macromolecular magnetization transfer (MT). Lorentzian fit isolation and application of the inverse metric yields the pure CEST contrast AREX, which is less affected by these processes, but still depends on the measurement technique, in particular on the irradiation amplitude B1 of the saturation pulses. This study focuses on two well-known CEST effects in the slow exchange regime originating from amide and aliphatic protons resonating at 3.5 ppm or −3.5 ppm from water protons, respectively. A B1-correction of CEST contrasts is crucial for the evaluation of data obtained in clinical studies at high field strengths with strong B1-inhomogeneities. Herein two approaches for B1-inhomogeneity correction, based on either CEST contrasts or Z-spectra, are investigated. Both rely on multiple acquisitions with different B1-values. One volunteer was examined with eight different B1-values to optimize the saturation field strength and the correction algorithm. Histogram evaluation allowed quantification of the quality of the B1-correction. Finally, the correction was applied to CEST images of a patient with oligodendroglioma WHO grade 2, and showed improvement of the image quality compared with the non-corrected CEST images, especially in the tumor region. Copyright © 2015 John Wiley & Sons, Ltd.